2021
DOI: 10.1016/j.ultsonch.2021.105711
|View full text |Cite
|
Sign up to set email alerts
|

The role of the particle size reduction and morphological changes of solid substrate in the ultrasound-aided enzymatic hydrolysis of cellulose

Abstract: Graphical abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…The reduction in particle size was also observed in sample from combination of freeze-thawing and ultrasonication (with the peak at 52 μm and 27 μm). The reduction of particle size could be attributed to the shearing forces from collapse of cavitation bubbles and high-velocity microjets during acoustic cavitation [38] . Numerous studies have also shown that ultrasound treatment led to a decrease in particle size of whey proteins [39] , soy proteins [40] and lupin proteins [41] .…”
Section: Resultsmentioning
confidence: 99%
“…The reduction in particle size was also observed in sample from combination of freeze-thawing and ultrasonication (with the peak at 52 μm and 27 μm). The reduction of particle size could be attributed to the shearing forces from collapse of cavitation bubbles and high-velocity microjets during acoustic cavitation [38] . Numerous studies have also shown that ultrasound treatment led to a decrease in particle size of whey proteins [39] , soy proteins [40] and lupin proteins [41] .…”
Section: Resultsmentioning
confidence: 99%
“…examined the hydrolysis of linen and cotton powders by a cellulase after different ultrasound pretreatments. The authors demonstrated a preferential hydrolysis of smaller particles by cellulases as well as a higher saccharification rate of substrates with a smaller particle size 24. Fernandes et al.…”
Section: Resultsmentioning
confidence: 97%
“…Csiszar et al examined the hydrolysis of linen and cotton powders by a cellulase after different ultrasound pretreatments. The authors demonstrated a preferential hydrolysis of smaller particles by cellulases as well as a higher saccharification rate of substrates with a smaller particle size [24]. Fernandes et al found an increase in glucose yield during enzymatic hydrolysis of sugarcane bagasse of 76 % with particles smaller than 60 mesh compared to native particle size [25].…”
Section: Biocatalysis Of Biomasses With Different Lignin Contentsmentioning
confidence: 98%
“…Among these alterations, a decrease in particle size of cellulose powder always accompanied by a significant increase in WHC, OHC, cholesterol adsorption and pancreatic lipase inhibition capacities. Because the decreased particle size can lead to an increase in surface area as well as the exposure of more hydrophilic and lipophilic groups, resulting in the increased binding ability of cellulose (Chen et al, 2013; Csiszar et al, 2021; Zheng et al, 2022). Therefore, the smaller particle size of MCC‐F seems to be much related with its better WHC, OHC and adsorption capacity when compared with MCC‐H.…”
Section: Resultsmentioning
confidence: 99%